Logistics Service Performance and Tourist Satisfaction in Salalah Tourism Industry: A Conceptual Framework - Inda Sukati; Shouvik Sanyal; Ali Mohsin Ba Awaain (International Journal of Supply Chain Management, 2020)
Abstract—This study examine the link between the quality of services provided by tourism supplier and tourist satisfaction. This research also investigates the moderating role of logistic service performance on the relationship between quality service provided by tourism supplier and tourist satisfaction. The objectives are as the follows: (a) Identify the dimensions of quality services provided by in tourism supplier and the performance of logistics services perceived by tourists; (2) Examine the linkage between the quality of service provided by tourism supplier to tourist satisfaction (3) propose theoretical framework and suggest for building the Salalah tourism industry become a better and can be one of unique tourist destination. The target respondents in this study are tourists come for tourist purpose stop at Salalah International airport, stay at hotels, apartments, and visit major tourist locations and shopping centres. The survey will explain to the tourists the purpose of conducting the survey and if they are willing to be a respondent, the questionnaire will be distributed for content and after filling out, the researcher will take the questionnaire for processing Keywords: Logistics service performance, quality service, tourism supplier, tourist satisfaction.